A Role Of Fabp1 And Eus As Diagnostic Tools For Pancreatic Steatosis (Journal of Pharmaceutical Negative Results, 2023)
Background: Pancreatic steatosis recently gain attention due to its relationship to metabolic disease and pancreatic cancer. The need for a non-invasive marker that can be utilized to aid in diagnosis is essential to add to the investigations, especially when used with imaging such as endoscopic ultrasound(EUS). Fatty acid binding protein 1 (FABP1) is a tissue-specific marker that can be used to diagnose NAFPD.Objective: The purpose of the current study was to determine the prevalence of NAFPD in obese and non-obese Egyptians with or without diabetes, evaluate any possible relationships between obesity, diabetes, or other metabolic risk factors, correlate pancreatic steatosis with non-alcoholic liver disease(NAFLD), and evaluate the diagnostic utility of FABP1 and EUS.Patients and methods: A prospective cohort study included 120 patients aged 18-70 years, who attended the outpatient clinic of the gastroenterology, hepatology, and Infectious Diseases Department at Al-Azhar University Hospital (Cairo) from January 2022 to October 2020. Patients were divided into 4 equal groups: Group 1: Healthy individuals with normal BMI and non-diabetic, Group 2: Patients with normal BMI, diabetics or impaired fasting blood glucose, Group 3: Patients with BMI over 25 non-diabetics, and Group 4: Patients with BMI over 25, diabetics or impaired fasting blood glucose level.Results: There was a positive correlation between FABP1 and pancreatic echogenicity, pancreatic steatosis is strongly associated with fatty liver and other metabolic risk factors.Conclusion: There is a strong link between pancreatic steatosis, metabolic syndrome, and NAFLD. EUS is superior in assessing pancreatic steatosis and has the potential to improve patient outcomes. As a biomarker, FABP1 can be used for non-alcoholic fatty pancreatic disease.